Incorporating equity, diversity and inclusion (EDI) into the education and assessment of professionalism for healthcare professionals and trainees: a scoping review - Shah, Darsh; Behravan, Nima; Al-Jabouri, Nujud; Sibbald, Matthew (BMC medical education, 2024)
Current definitions of professionalism for healthcare trainees often lack equity, diversity and inclusion (EDI) in the expectations and assessment of professionalism. While professionalism teaching is incorporated in healthcare training, equity-deserving groups still experience discrimination. This scoping review investigates the literature to understand how EDI and associated domains of cultural humility, and advocacy can be incorporated in healthcare trainees' education and assessment of professionalism. The Arksey and O'Malley framework was applied to this scoping review. MEDLINE, Embase & PsychINFO were searched up to March 2023, with terms surrounding health professionals, professionalism, EDI, cultural humility, and advocacy. Titles and abstracts (n = 3870) and full-texts (n = 140) were independently screened by two reviewers. Articles were included if they focused on EDI, cultural humility, or advocacy among healthcare students/trainees, and had outcomes related to professionalism. Articles lacking discussion of professionalism as an outcome were excluded. Themes were generated by mutual discussion. Risk of bias was assessed using the Cote et al. and Medical Education Research Study Quality Instrument (MERSQI) tools. 48 articles underwent thematic analysis. Studies investigated the disciplines of medicine, nursing, social work, physiotherapy, and dentistry. Most studies were qualitative in methodology (n = 23). Three themes emerged: (1) EDI-related interventions are associated with improved professionalism of healthcare trainees/workers (n = 21). Interventions employed were either an EDI-associated educational course (n = 8) or an exchange program to promote EDI competencies among trainees (n = 13). (2) Trainee definitions and perceptions of professionalism include themes related to EDI and cultural humility (n = 12). (3) Current standards of professionalism are perceived as non-inclusive towards historically-marginalized populations (n = 15). Literature investigating advocacy as it relates to professionalism is limited. This review identified that core EDI principles and its associated domains of cultural humility and advocacy are often viewed as integral to professionalism. These findings create a strong impetus to incorporate EDI principles within professionalism frameworks in healthcare education. Future research should employ standardized tools for professionalism assessment to provide more conclusive evidence. Incorporating patient perspectives of professionalism can inform actionable recommendations for fostering inclusive healthcare environments.